Photocatalytic Performance Of G-C3n4 Ag-Metal Oxides Photocatalysts For Degradation Of Reactive Black 5 Rb5 And Phenol Under Simulated Solar Light - Rosli, Noor Izzati Md. (2020)
Environmental pollution by various hazardous contaminants can give a negative effect to the environment and living organisms. A class of Advanced oxidation process (AOP) called heterogeneous photocatalysis by g-C3N4 photocatalyst has attracted recent years for wastewater purification. However, g-C3N4 alone suffered from high recombination rate of e-/h+ pairs which can inhibit its photoactivity. Thus, semiconductor coupling of g-C3N4 with a different energy level of semiconductor has been proposed in this study. A series of g-C3N4/Ag-metal oxides (Ag-metal oxides = AgFeO2, Ag4V2O7 and Ag2Mo2O7) photocatalyst was developed to study the photocatalytic degradation of Reactive Black 5 (RB5) and phenol under simulated solar light. The developed photocatalysts were denoted as BCN, AVO/BCN, AMO/BCN and AFO/BCN photocatalysts corresponding to the pure g-C3N4, g-C3N4/Ag4V2O7, g-C3N4/Ag2Mo2O7 and g-C3N4/AgFeO2, respectively. The developed photocatalysts were characterized by X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Diffuse Reflectance Spectra (UV-vis DRS) and BET surface area measurements to determine their physical, chemical and optical properties. Photocatalytic assessment revealed that g-C3N4/Ag-metal oxides photocatalyst exhibited high photocatalytic performance for RB5 degradation. Particularly, g-C3N4/Ag2Mo2O7 photocatalyst exhibited the highest photocatalytic activity with 97% degradation of RB5 was achieved, while g-C3N4/Ag4V2O7 and g-C3N4/AgFeO2 photocatalysts exhibited 83% and 77%, respectively. Mechanistic study suggested as-prepared photocatalyst followed a Z-scheme mechanism. Compared to pure g-C3N4, the photoluminescence (PL) spctra of g-C3N4/Ag-metal oxides showed a significant decrease of photoluminescence intensity of charge carriers and a suitability of redox potential of the two semiconductors to produce •OH radicals. This implication as proven by the radical scavengers test and terapththalic-acid (TA-PL) experiments. XRD result showed that g-C3N4/Ag-metal oxides photocatalysts exhibited high crystallinity. SEM finding revealed that the formation of 1D structure of AMO/BCN photocatalyst could provide a high surface to volume ratio which were advantages to the photocatalytic activity. UV-vis absorption result showed that the incorporation of Ag-metal oxides can facilitate in absorbing more light energy, hence enhancing the optical properties. Various operational process parameters were studied, and the findings demonstrated that 99% of RB5 was degraded under 1.0 g/L of photocatalyst loading, 10 mg/L of RB5 and pH solution of 3. Meanwhile, at 106.5 mg/L of oxidant 1.0 g/L of photocatalyst loading, 5 mg/L of phenol and pH solution 5.7, 98% of phenol was degraded. Mineralization study showed that both RB5 and phenol can be mineralized under their best condition. The kinetic study demonstrated that degradation of RB5 and phenol followed a Langmuir-Hinshelwood (L-H) first-order kinetic model. The AMO/BCN photocatalyst can reduced the electrical energy consumption for degradation of RB5 and phenol as compared to those of commercial TiO2 photocatalyst. Sunlight photocatalytic activity suggested that AMO/BCN photocatalyst was an active photocatalyst under sunlight irradiation.